2022
DOI: 10.1097/bpo.0000000000002204
|View full text |Cite
|
Sign up to set email alerts
|

3D Gait Analysis and Patient-reported Outcomes of Femoral Osteotomies for Torsional Deformity

Abstract: Background: Idiopathic torsional deformities causing pain and/or functional difficulty is an indication for a femoral derotational osteotomy (FDRO). Past studies have focused entirely on children with internal femoral torsional deformity (IFTD). This study aims to compare gait and outcomes between children with IFTD and those with external femoral torsional deformity (EFTD) after a FDRO. Methods: A retrospective review of all patients who underwent an FDRO between 1997 and 2020 at our institution. Data on typi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
(93 reference statements)
1
3
0
Order By: Relevance
“…In FA, hip rotation allows neutral knee progression but results in relatively internal foot progression. This knee progression strategy correlates with the recent work by Hamid et al demonstrating the compensatory mechanism of increased internal hip rotation to optimize the abductor moment [11].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In FA, hip rotation allows neutral knee progression but results in relatively internal foot progression. This knee progression strategy correlates with the recent work by Hamid et al demonstrating the compensatory mechanism of increased internal hip rotation to optimize the abductor moment [11].…”
Section: Discussionsupporting
confidence: 87%
“…More recently, 3-dimensional motion analysis has provided increased insight into quantifying and characterizing these deformities [8][9][10][11]. Level walking at a self-selected speed may not exhibit large deviations from typically developing (TD) children due to compensatory mechanics, including hip rotation and alterations in ground reaction force loading to correct moments.…”
Section: Introductionmentioning
confidence: 99%
“…Hamid et al used the pediatric outcomes data collection instrument to investigate changes in PROMs following this procedure. 11 They noted improvements in transfer/basic mobility, sports/physical function, global functioning, and satisfaction with symptoms in their internal torsional deformity patients. In their external torsional deformity patients, they noted an improvement in satisfaction with symptoms after surgery.…”
Section: Discussionmentioning
confidence: 97%
“…Hamid et al reported improved 3D gait analysis and Pediatric Outcomes Data Collection Instrument (PODCI) scores following surgical correction of femoral torsion in patients with internal and external femoral torsional deformities 30 . A survey of 461 surgeons using the Hospital for Special Surgery Knee Surgery Expectations Survey (HFSS-KSES) and a 10-item, non-validated questionnaire evaluated surgeons' expectations and compared these with patient expectations regarding the results of high tibial osteotomies 31 .…”
Section: Lower-extremity Deformitymentioning
confidence: 99%